2016
DOI: 10.1016/j.mrgentox.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminoantipyrine reduces toxic and genotoxic effects of doxorubicin, cisplatin, and cyclophosphamide in male mice

Abstract: The analgesic drug dipyrone is used to treat side effects (including pain and fever) of cancer chemotherapeutic agents. Dipyrone is metabolized to 4-aminoantipyrine (4-AA), a PGE2-dependent blocker and inhibitor of cyclooxygenase (COX). We evaluated the genotoxic, mutagenic, apoptotic, and immunomodulatory activities of 4-AA in vivo and the effects of its combination with the antineoplastic drugs doxorubicin, cisplatin, and cyclophosphamide. 4-AA did not cause genotoxic/mutagenic damage, splenic phagocytosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 23 publications
6
21
4
Order By: Relevance
“…It should be stressed, however, that 72 hours after the treatment, the positive control no longer showed a significant difference regarding the presence of micronuclei in relation to the other treatments, indicating that although this is within the range of time recommended by the OECD TG 474 (2014), it is not efficient to analyze the results when using cyclophosphamide as positive control at a concentration of 50 mg/kg. A reduction of the number of micronucleated erythrocytes with longer time interval after application of the drug has also been reported by other authors (Berno et al, 2016;Schneider et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…It should be stressed, however, that 72 hours after the treatment, the positive control no longer showed a significant difference regarding the presence of micronuclei in relation to the other treatments, indicating that although this is within the range of time recommended by the OECD TG 474 (2014), it is not efficient to analyze the results when using cyclophosphamide as positive control at a concentration of 50 mg/kg. A reduction of the number of micronucleated erythrocytes with longer time interval after application of the drug has also been reported by other authors (Berno et al, 2016;Schneider et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…In this case, the properties derived from 4-aminoantipyrine, even when in combination with the 1,4-dioxo-butenyl fragment, recognized as cytotoxic ( Jha et al , 2010 ), largely overrode the ability to induce cell death. Corroborating this, the study by Berno et al (2016) states that 4-aminoantipyrine, a dipyrone metabolite, reduces DNA damage, apoptosis induction and phagocytosi when administered in combination with doxorubicin, cisplatin or cyclophosphamide.…”
Section: Discussionmentioning
confidence: 95%
“…The increase of cells with NCCA and genomic chaos in the samples after treatment is evident and undoubtedly, their origin is complex and multifactorial. There is a large amount of bibliography that shows that the agents used in chemotherapy and radiotherapy in our patients are clearly genotoxic and induce CA in noncancerous cells; the genotoxicity is documented in different type of cells (for review, see Frias et al 2019), as well as in murine models without viral infections (Berno et al 2016). Thus, we concluded that the genotoxicity of anticancer treatment was a major player in the origin of cells with NCCA and genomic chaos that we observed.…”
mentioning
confidence: 99%